On determination of Sun-rise/set time and on construction of a Computer for the purpose (MAUSAM, 1964)
A simple sliding computer determine sun rise/set times for any place within Indian latitudes is described. Its mathematical basis is discussed. A rough and ready method based on Variation of Sun-rise/set times with latitude is also mentioned, Variation in the observed times of sun-rise/set time with latitude is discussed and its importance to aircraft pilots indicated.